Fundamentalism on stilts: A response to Alvin Platinga’s reformed epistemology - Gericke, Jaco S. (Verbum et ecclesia, 2009)
During the greater part of the 20th century, biblical scholarship and the philosophy of religion were not considered to have much in common. However, towards the end of the millennium, a movement of a few Christian philosophers of religion called ‘Reformed Epistemology’ (RE) suggested the need for interdisciplinary dialogue. With Alvin Plantinga as primary representative, these philosophers claimed to be concerned with what they considered to be the lack of philosophical reflection on the foundations of historical criticism and its non-traditional findings. In this article, the author (qua biblical scholar) suggests that Plantinga’s arguments have not been taken seriously because of his fundamentalism and the resulting failure to grasp the nature and contents of the hermeneutical debates that have raged within biblical theology for the past 200 years.